APPLICATION OF INDUSTRY 4.0 TECHNOLOGIES IN HOME DELIVERY: A REVIEW - Tadić, Snežana; Veljović, Miloš; Krstić, Mladen; Zečević, Slobodan (Journal of Applied Engineering Science, 2023)
The development of the Internet has accelerated the development of electronic commerce, which has led to changes in the management of supply chains and logistics. Unlike traditional shopping trips, there is a need for home deliveries and appropriate logistics systems for their implementation. To overcome new challenges and achieve process efficiency and the quality of home delivery service, there is a need for individual or integrated application of various Industry 4.0 technologies such as the internet of things, additive manufacturing, autonomous vehicles, blockchain, big data, data mining, artificial intelligence, virtual and augmented reality, etc. Accordingly, this paper aims to provide a comprehensive overview and description of the application of technological solutions of Industry 4.0 in home delivery. This goal is achieved through a comprehensive literature review on the topic. The results indicate that although a large number of studies in the literature dealt with the application of individual or integrated Industry 4.0 solutions in home delivery or last-mile logistics, a comprehensive review of the application of existing solutions in home delivery has not been carried out so far. This is thereby the main contribution of this paper. Overview of the technologies application provides a basis for identification of those that have the widest possibilities and generate the most positive effects, and should thus be the focus of future studies and development plans.
Keywords: last mile, home delivery, industry 4.0, Logistics 4.0, technologies